The Role of Aisyah Bint Abi Bakar as a Critic in Hadith Narration - Mustikawati, Mustikawati; Dadah, Dadah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Hadiths have been revealed by many friends, including one of the believers, Aisyah bin Abu Bakar ra. She is a fairy hadith woman who gives many insights and criticisms of the hadiths brought by the friend. This writings reveal some of the criteria used by Aisyah in establishing the month of Hadith to be acceptable. The research method used is the library research of both books, books, articles and journals. The criterion of the month of a hadith is that it does not contradict the Qur'an, the hadith of the great, as well as the understanding